Infants use helping to infer the existence and strength of caring relationships - Bill Pepe; Brandon M. Woo; Ashley J. Thomas; Lindsey J. Powell (Proceedings of the National Academy of Sciences, 2026)
Prosocial and antisocial behaviors can reflect the actor’s positive or negative feelings toward a specific person and their broader disposition toward others’ welfare. Observers’ inferences about these motives shape what they learn about the actor’s social relationships and moral character, thereby informing expectations about the actor’s future behaviors. In four preregistered studies, we used violation-of-expectation looking methods to investigate 14- and 15-mo-old infants’ inferences about social motives by first showing them helping and hindering events and then assessing their expectations for those actors’ future actions. If infants use helping and hindering to infer disposition-based motives, they should extend expectations about future helping to others. Alternatively, if they infer relationship-based motives, their expectations should be restricted to the initial interactants. In Experiments 1 and 2, infants first observed two actors, one who helped and another who hindered a common target. At test, infants expected the helper would help the same target in a new, perceptually distinct situation. However, this expectation did not generalize to a new target, suggesting infants inferred specific relationships, not general dispositions. In Experiments 3 and 4, we assessed whether infants used information about the existence or strength of a helper’s relationships to predict who they would prioritize helping in the future. We found that infants used patterns of selective helping among multiple targets to make transitive inferences about whose needs the helper would prioritize. Taken together, this suggests that infants use such observations of helping to infer whether, and how much, the helper cares for their social partner.